Parametric aqueous electrodeposition study and characterization of Fe–Cu films. (20th March 2017) - Dislaki, Evangelia; Sort, Jordi; Pellicer, Eva
Abstract: In this study, Fex Cu1−x films over a wide composition range (0≤x≤86) were prepared from an aqueous sulfate electrolytic solution using three different complexing agents and variable plating conditions. The effect of parameters such as bath composition, current density and temperature on the elemental composition, morphology, structure and magnetic properties of the deposits was investigated. The electrochemical behavior was studied using cyclic voltammetry. High quality, smooth deposits with good substrate adhesion and minimized oxygen content were achieved. X-ray patterns indicate phase separation, though results from Rietveld analysis strongly suggest partial alloying. Magnetization dependence on Fe content is clearly demonstrated.